2012
DOI: 10.1590/s0080-62342012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Criança dependente de tecnologia: a experiência do cuidado materno

Abstract: RESUMOEste estudo tem como obje vo compreender a experiência materna no cuidado ao fi lho dependente de tecnologia. U lizamos a abordagem do estudo de caso etnográfi -co tendo como instrumentos de coleta de dados os genograma e ecomapa, entrevista aberta e observação. Os dados foram organizados em três unidades de signifi cados: a busca pelas causas e por culpados; a alta hospitalar e as demandas para o cuidado e as redes de apoio. O estudo permi u conhecer a experiência materna em busca por explicações, bem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 9 publications
0
19
0
7
Order By: Relevance
“…They talk about sleep that is frequently interrupted by equipment alarms or the need to give a child medicine through the night. Another situation is the difficulty parents have relaxing, as often other family members or friends do not have the training required to provide this complex care, resulting in caregivers falling ill (11)(12)(13)(14)(15) . Here we find that instrumental and emotional support by the family network is weak.…”
Section: Discussionmentioning
confidence: 99%
“…They talk about sleep that is frequently interrupted by equipment alarms or the need to give a child medicine through the night. Another situation is the difficulty parents have relaxing, as often other family members or friends do not have the training required to provide this complex care, resulting in caregivers falling ill (11)(12)(13)(14)(15) . Here we find that instrumental and emotional support by the family network is weak.…”
Section: Discussionmentioning
confidence: 99%
“…In order to strengthen the autonomy of the CSHCN family members dependent on technology, the scientific literature showed that nursing is deci-sive in the hospitalization process, which can contribute to the development of knowledge and skills in home care, and these professionals are fundamental in the transition process from the hospital to the home. 18 Thus, it is necessary to think of educational actions as inherent and inseparable from the hospital care, from a perspective of action-reflection-action, a dialogic action that is conscientious. 9 With the analysis of the testimonies, it was noticed that home care is sometimes more complex than hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…Vale destacar que os familiares, no decorrer da doença, adquirem experiências que são somadas aos valores, crenças e costumes familiares, o que influencia no cuidado prestado à criança (23). Assim, os familiares precisam apreender e desenvolver novas estratégias para manter a alimentação de suas crianças que tiveram os hábitos alimentares modificados devido ao tratamento quimioterápico.…”
Section: Discussionunclassified